The Tears of the Black Man - Mabanckou, Alain, 1966- (Book collections on Project MUSE., 2018)
Embracing the challenges faced by ethnic minority communities today, The Tears of the Black Man looks to the future, arguing that the history of Africa has yet to be written and seeking a path toward affirmation and reconciliation.